2014
DOI: 10.1128/aac.02137-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Membrane Transporter Mediating Resistance to Organic Arsenic in Campylobacter jejuni

Abstract: Although bacterial mechanisms involved in the resistance to inorganic arsenic are well understood, the molecular basis for organic arsenic resistance has not been described. Campylobacter jejuni, a major food-borne pathogen causing gastroenteritis in humans, is highly prevalent in poultry and is reportedly resistant to the arsenic compound roxarsone (4-hydroxy-3-nitrobenzenearsonic acid), which has been used as a feed additive in the poultry industry for growth promotion. In this study, we report the identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 41 publications
(52 reference statements)
0
30
0
2
Order By: Relevance
“…The arsP gene from C. jejuni confers resistance to trivalent organoarsenicals Cells of C. jejuni expressing the arsP gene have been shown to exhibit resistance to pentavalent roxarsone and nitarsone (Shen et al, 2014). In this study, the CjarsP gene was cloned downstream of the trc promoter in plasmid pTrcHis2A and expressed in the arsenitehypersensitive E. coli strain AW3110, in which the chromosomal arsRBC operon was deleted (Carlin et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The arsP gene from C. jejuni confers resistance to trivalent organoarsenicals Cells of C. jejuni expressing the arsP gene have been shown to exhibit resistance to pentavalent roxarsone and nitarsone (Shen et al, 2014). In this study, the CjarsP gene was cloned downstream of the trc promoter in plasmid pTrcHis2A and expressed in the arsenitehypersensitive E. coli strain AW3110, in which the chromosomal arsRBC operon was deleted (Carlin et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Shen et al . () demonstrated that the arsP gene of C. jejuni is responsible for roxarsone resistance. They showed that ArsP is a permease that results in lowered roxarsone in the cells of C. jejuni .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified ArsH from either S. meliloti or P. putida are yellow and show a typical flavoprotein absorption spectrum. 63,66 P. putida oxidized MAs(III), PhAs(III) and Rox(III). 64 The crystal structure of S. meliloti ArsH (Figure 5) was determined at 1.8 Å resolution and is similar to other flavoproteins.…”
Section: Arsh a Mas(iii) Oxidasementioning
confidence: 99%
“…It has been determined that Campylobacter mediates much of its antibiotic resistance through a multidrug efflux system, CmeABC (Lin et al, 2002). However, studies have demonstrated that these genes do not confer additional antibiotic resistance (Shen et al, 2013(Shen et al, , 2014Wang et al, 2009). However, studies have demonstrated that these genes do not confer additional antibiotic resistance (Shen et al, 2013(Shen et al, , 2014Wang et al, 2009).…”
Section: Coccidostat Usage and Arsenic Resistancementioning
confidence: 99%